2020
DOI: 10.7575/aiac.alls.v.11n.1p.55
|View full text |Cite
|
Sign up to set email alerts
|

The Level and Sources of Foreign Language Speaking Anxiety among Saudi EFL University Students

Abstract: This study aims to investigate the level and the sources of Foreign Language Speaking Anxiety (FLSA). To achieve this aim, a mixed-method approach was used by implementing a questionnaire and interviews. Eighty-five female Saudi EFL university students completed the questionnaire. Six of the most highly anxious students were identified according to the questionnaire results and interviewed. The findings revealed that the participants experienced a moderate level of FLSA in their English class. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 23 publications
7
32
0
Order By: Relevance
“…In addition, results of their research describe that the low selfconfidence factor accepted the highest average attended by fear of bad evaluation and communication apprehension element. Other studies conducted by Alnahidh and Altalhab [32] , and Sugiyati and Indriani [33] found that the level of moderate in Foreign Language Anxiety Scale of participants in English Class. Any time, when they performed speaking in the class, they already dealt with the anxiety.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, results of their research describe that the low selfconfidence factor accepted the highest average attended by fear of bad evaluation and communication apprehension element. Other studies conducted by Alnahidh and Altalhab [32] , and Sugiyati and Indriani [33] found that the level of moderate in Foreign Language Anxiety Scale of participants in English Class. Any time, when they performed speaking in the class, they already dealt with the anxiety.…”
Section: Discussionmentioning
confidence: 84%
“…Conversely, highly anxious learners use expressions in a nervous or tense way specially in an evaluative circumstance (Liu, 2018). Furthermore, Toubot and Seng (2018), Alnahidh and Altalhab (2020) found that students suffer from moderate to high level of FLA. Recently, Saghafi and Shirvan (2020) found that patterns of anxiety were not the same among the learners and within the same learner in the speaking tasks.…”
Section: Foreign Language Speaking Anxietymentioning
confidence: 97%
“…Conversely, commonly shy and reserved speakers while speaking in foreign language may have developed a different sense of self in the target language and feel as if they are not talking, but somebody else is talking and this results in a reduction of anxiety (Horwitz et al, 1986). In addition, CA is the concern that learners experience in oral communication (Alnahidh & Altalhab, 2020), for instance, in speaking activities, students may feel embarrass and worry to perform well. In this regard, communication apprehension is caused by personality traits such as shyness, calmness, and fear of making mistakes (Toubot & Seng, 2018).…”
Section: Foreign Language Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple dictionary definitions describe anxiety as the condition of feeling apprehensive or terrified that maybe something unpleasant may transpire, or a sensation of tension and concern about something (Merriam-Webster, 2019;Pearson Education, 2014;Oxforward University Press, 2011). Moreover, Alnahidh and Altalhab (2020) termed anxiety as "the subjective sensation of tension, apprehension, uneasiness, and concern connected with an activation of the autonomic nervous system." From such a psychological standpoint, it is evident that anxiety would be regarded as a specific emotional disorder that has a detrimental effect on human conduct as the substantial focus of this research (Coppinger & Sheridan, 2022;Kiae et al, 2021).…”
Section: Anxiety-psychological Disordermentioning
confidence: 99%